Manabi: territory with food potential in times of covid-19 - Loor Cedeño, Pablo; Bravo Vélez, Diana; Gómez García, Susetty Lorena; Jimenez Mendoza, Dolores (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December)DO - 10.36779/mktdescubre.v1i18.629, 2021)
Agricultural activities are a factor of wealth and accumulation. Producing food requires intensifying productive potential. Manabí, affected by the covid-19 pandemic, has had various difficulties; however, public and private entities carried out actions in favor of farmers; allowing food production to supply the local and regional market. In this context, the research problem to answer: Is Manabí a territory with food potential in times of Covid - 19? To answer this question, the objective of the research is to show the potential of Manabí in food production in times of pandemic. Methodologically, this research is descriptive and qualitative based on bibliographic, documentary and field studies. To obtain primary information, surveys were applied to the producers, to know the strengths and weaknesses of agricultural activities. The results show that, to strengthen productive capacities, it is necessary to carry out technological innovations that allow increasing production and productivity, to achieve competitiveness in quality and price. Agricultural activity is essential within economies as it is a source of income and guarantees food security. Conclusively, Manabí has a diversity of soils and climates for a varied agricultural production.